INNER CHARACTERIZATION OF THE MAIN CHARACTER IN THE NOVEL “THE WINGS OF THE DOVE” BY HENRY JAMES (Conferencea, 2022)
In the article inner characterization of the main character, Milly Theale in the novel “The Wings of the Dove” by Henry James is discussed in the paper.